A New and Rapid LC-MS/MS Method for the Determination of Cysteamine Plasma Levels in Cystinosis Patients - Raffaele Simeoli; Sara Cairoli; Marcella Greco; Francesco Bellomo; Alessandro Mancini; Chiara Rossi; Carlo Dionisi Vici; Francesco Emma; Bianca Maria Goffredo (MDPI AG, 2024)
Cystinosis is a rare lysosomal storage disorder caused by autosomal recessive mutations in the CTNS gene that encodes for the cystine transporter cystinosin, which is expressed on the lysosomal membrane mediating the efflux of cystine. Cysteamine bitartrate is a cystine-depleting aminothiol agent approved for the treatment of cystinosis in children and adults. In this study, we developed and validated a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the determination of cysteamine levels in plasma samples. This LC-MS/MS method was validated according to the European Medicines Agency (EMA)'s guidelines for bioanalytical method validation. An ultra-performance liquid chromatograph (UPLC) coupled with a 6470 mass spectrometry system was used for cysteamine determination. Our validated method was applied to plasma samples from n = 8 cystinosis patients (median, interquartile range (IQR) = 20.5, 8.5-26.0 years). The samples were collected before cysteamine oral administration (pre-dose) and 1 h after (post-dose). Our bioanalytical method fulfilled the regulatory guidelines for method validation. The cysteamine plasma levels in pre-dose samples were 2.57 and 1.50-3.31 μM (median and IQR, respectively), whereas the post-dose samples reported a cysteamine median concentration of 28.00 μM (IQR: 17.60-36.61). Our method allows the rapid determination of cysteamine plasma levels. This method was successfully used in cystinosis patients and, therefore, could be a useful tool for the evaluation of therapy adherence and for future pharmacokinetic (PK) studies involving a higher number of subjects.